Menimbang keseimbangan hak dan kewajiban antara negara dan warga negara di tengah krisis kepercayaan publik - Masruroh, Ana Faizatul (Maliki Interdisciplinary Journal, 2025)
This article discusses the imbalance between the fulfillment of rights and obligations in the relationship between the Indonesian state and its citizens amid a public trust crisis. The state often demands consistent obligations from citizens, such as paying taxes and obeying the law, while at the same time failing to fairly provide basic rights such as legal protection, welfare, and adequate public services. This study uses a qualitative approach through literature study aimed at examining the dynamics of the imbalance and its impact on state legitimacy. The results show that the public trust crisis worsens the gap between state and citizens, and decreases political and social participation. Therefore, efforts to rebuild public trust through institutional reform and civic education are crucial to maintaining national integration.